A review of bio-oil upgrading by catalytic hydrodeoxygenation - Tran, N. (Trans Tech Publications Ltd, 2014)
Fast pyrolysis is an attractive thermal conversion process to generate the alternative liquid fuel. However, the bio-oil obtained from biomass pyrolysis has polarity, instability and low energy density due to contained oxygenated compound. Hydrodeoxygenation (HDO) process is the most promising route for bio-oil upgrading through oxygen elimination. The products are suitable for co-feeding into the existing refineries. Metal catalyst and operating conditions play an important role in HDO efficiency. A summary of HDO process has been conducted with various metal catalysts, type of reactors, and reaction mechanisms. It also raises some challenges in improving catalyst efficiency, reducing hydrogen consumption, and effort to understand the HDO kinetics. Â© 2014 Trans Tech Publications, Switzerland.